A Three-Aspect Model for Consciousness - Graboi, Dan (Journal of Scientific Exploration, 2023)
A model for consciousness is proposed based on Nisargadatta Maharaj ‘s interpretation of Jnana Yoga/Advaita Vedanta. Concepts from modern physics, neuroscience, and information science are integrated into that framework. A novel understanding of information in the context of a system with consciousness is proposed. Information generated in the neurophysiology of a brain’s unique “wiring structure” is hypothesized to become dissociated from the neurophysiology and transformed into a universal format within a nonphysical domain in which consciousness is assumed to occur. Sharing features with Bohm’s Implicate Order, the nonphysical domain has nonlocal properties which support instant correlation of information throughout. The energy of a carrier is not needed to transport information in the nonphysical domain. This allows for low-energy neurological systems to transfer information associated with thought across large distances, as observed in telepathic psi phenomena. An experiment to test for the existence of a nonphysical dimension that supports instant telepathic information transfer is discussed. It is argued that three is the minimum number of aspects necessary to model a practical framework for consciousness.